Wakefield acceleration. State and prospects (Оverview) - Onishchenko, I.N.; Pristupa, V.I. (Вопросы атомной науки и техники, 2017)
The results of researches on the wakefield method of high-gradient acceleration of charged particles carried out within the framework of the projects “FACET” (SLAC), “BELLA” (LNBL), “AWAKE” (CERN) and in other laboratories, including NSC KIPT, are presented. The acceleration of charged particles in a plasma wakefield with acceleration rate up to 100 GeV/m excited by an intense electron bunch (PWFA) or by a powerful laser pulse (LWFA), and in a dielectric wakefield with acceleration rate up to 1 GeV/m excited by an intense electron bunch (DWFA) is considered.